Circles and Trapezoids

Level pending

Let b > a b > a .

A circle with radius r r is inscribed in a right trapezoid with base lengths a a and b b and the larger circle with radius R R goes thru the vertices P , Q , T P,Q,T of the right trapezoid as shown above.

Let h h be the height of the right trapezoid.

If R 2 h = 2 a b 3 + b 4 4 ( a + b ) 2 R^2 - h = \dfrac{2ab^3 + b^4}{4(a + b)^2} , find r + h r + h .


The answer is 4.8.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Rocco Dalto
Sep 23, 2018

For smaller circle:

( a + b 2 r ) 2 = ( 2 r ) 2 + ( b a ) 2 a 2 + 2 a b + b 2 4 ( a + b ) r + 4 r 2 = 4 r 2 + b 2 2 a b + a 2 4 a b = 4 ( a + b ) r 2 (a + b - 2r)^2 = (2r)^2 + (b - a)^2 \implies a^2 + 2ab + b^2 - 4(a + b)r + 4r^2 = 4r2 + b^2 - 2ab + a^2 \implies 4ab = 4(a + b)r^2

r = a b a + b \implies \boxed{r = \dfrac{ab}{a + b}}

For outer circle ( x x 0 ) 2 + ( y y 0 ) 2 = R 2 (x - x_{0})^2 + (y - y_{0})^2 = R^2 .

Using the three points on the larger circle I chose above:

( 0 , 0 ) : x 0 2 + y 0 2 = R 2 (0,0): x_{0}^2 + y_{0}^2 = R^2

( 0 , 2 r ) : x 0 2 + 4 r 2 4 r y 0 + y 0 2 = R 2 4 r ( r y 0 ) = 0 r 0 y 0 = r = a b a + b (0,2r): x_{0}^2 + 4r^2 - 4ry_{0} + y_{0}^2 = R^2 \implies 4r(r - y_{0}) = 0 \:\ r \neq 0 \implies y_{0} = r = \dfrac{ab}{a + b}

( b , 0 ) : b 2 2 b x 0 + x 0 2 + y 0 2 = R 2 x 0 = b 2 (b,0):b^2 - 2bx_{0} + x_{0}^2 + y_{0}^2 = R^2 \implies x_{0} = \dfrac{b}{2}

R 2 = b 2 4 + a 2 b 2 ( a + b ) 2 \implies \boxed{R^2 = \dfrac{b^2}{4} + \dfrac{a^2b^2}{(a + b)^2}}

The height of the trapezoid h = 2 r = 2 a b a + b h = 2r = \dfrac{2ab}{a + b} \implies

R 2 h = b 2 4 + a 2 b 2 ( a + b ) 2 2 a b a + b = R^2 - h = \dfrac{b^{2}}{4} + \dfrac{a^2b^2}{(a + b)^2} - \dfrac{2ab}{a + b} = 5 a 2 b 2 + 2 a b 3 + b 4 8 a 2 b 8 a b 2 4 ( a + b ) 2 = 2 a b 3 + b 4 4 ( a + b ) 2 \dfrac{5a^2b^2 + 2ab^3 + b^4 - 8a^2b - 8ab^2}{4(a + b)^2} = \dfrac{2ab^3 + b^4}{4(a + b)^2} \implies a b ( 5 a b 8 a 8 b ) = 0 a , b 0 5 a b = 8 ( a + b ) r = a b a + b = 8 5 r + h = 3 r = 24 5 = 4.8 ab(5ab - 8a - 8b) = 0 \:\ a,b \neq 0 \implies 5ab = 8(a + b) \implies r = \dfrac{ab}{a + b} = \dfrac{8}{5} \implies r + h = 3r = \dfrac{24}{5} = \boxed{4.8} .

The square sign looks fine by me.

Pi Han Goh - 2 years, 8 months ago

Log in to reply

Thanks, although now it is not distorted. Must be my computer.

Actually, I just noticed that if I view your comment, then it's not distorted, but if I go to my profile it is distorted. I'm at a loss to explain it.

Rocco Dalto - 2 years, 8 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...